Protecting Privacy in Location-Based Services Through Location Anonymization Using Cloaking Algorithms Based on Connected Components - Saravanan, P. Shanthi; Balasundaram, S. R. (Wireless personal communications, 2018)
With ever increasing advances in Information and Communication Technologies, location-based services (LBS) have obtained significant attention and popularity. However the services are provided at the cost of exposing the location-context of users, which exposes privacy and security threats to users. This paper presents an efficient location privacy-preserving solution based on location cloaking. Specifically to cloak location-contexts a new component based graph model called Cloaked Region Construction Algorithm (CRCA) is proposed, which can group users in the closer location proximity. To obtain an optimal cloaked region, heuristic search based on the center of spanning tree technique is used. Further, Dice’s coefficient is used to find LBS query similarities that help to avoid query similarity attacks. Through component based graph structure, optimal sub-group selection and query diversity, the proposed CRCA protects users’ location privacy to a greater extend while maintaining the quality of the query service. Experimental results show that CRCA performs well on providing high degree of privacy protection with a reasonably-sized cloaked region, and a high cloaking success rate.